IMPLEMENTATION OF PRISONERS' SELF-GUIDANCE DEVELOPMENT AT PENITENTIARY INSTITUTIONS TO ERADICATE NEGATIVE STIGMA - Febrianto, Dewa Dermawan (Bisma The Journal of Counseling, 2020)
In Law 12 of 1995 concerning Correctional, it is explained that the convict is someone who has obtained permanent legal force from the court for violating the law he commited and placed in a correctional institution. In undergoing their criminal term in correctional institution they receive guidance in order to realize their mistakes, improve themselves, and no longer to repeat their criminal acts, so that they can be readmitted into the community. In the process of their return to the community, many of them were struggled to adapt again, because of  negative stigmatization of the community. The impact is they will find hard to get a decent job, will be exclude from the community, and even worse they will did their crime again. In correctional institution there is a term for recidivist or a term for those ex-convict who have been released but go back again into correctional institution  for repeating their crime. In this case many opinions from outside assume if the coaching process was given did not go well or failed. So in the study will discuss how to disperse the negative stigma of ex-convicts through the implementation results of the guidance that has been given into the community.